Thermally treated lanthanum oxide nanoparticles-embedded polyamide composite nanofiber membrane for enhanced mechanical properties and phosphorus adsorption kinetics - Choi, Yun Young; Cwiertny, David M.; Myung, Nosang V. (Frontiers in Chemistry, 2025)
Lanthanum oxide (La2O3) nanoparticles-embedded polyamide 6 nanofiber membranes were electrospun using hexafluoroisopropanol (HFIP) as the solvent. Unlike other solvents such as formic acid and an acetone: trifluoroacetic acid (ace: TFA) mixture, HFIP allowed La2O3 nanoparticles to remain well-suspended without altering their composition. Various material characterizations confirmed La2O3 nanoparticles are well embedded in polyamide nanofibers. The phosphorus uptake capacity remains consistent when La2O3 nanoparticles were embedded in polyamide 6 nanofibers (∼10.4 mg/g) compared to free suspended nanoparticles (∼10.3 mg/g). By optimizing post-thermal treatment, both mechanical strength (e.g., yield strength (σy) from 1.68 × 107 to 2.67 × 107 Pa) and adsorption kinetics (e.g., k2 from 2.63 × 10−2 to 1.49 × 10−1 g/(mg·min)) were improved. This study confirms that post thermal processing can be used to further enhance the mechanical properties of the composite nanofiber membrane while maintaining its phosphate adsorption capabilities and improved adsorption kinetics.